Perceived tangible value, customer satisfaction and post-purchase action in off-premise catering / Siti Nurhanifah Sulong - Sulong, Siti Nurhanifah (2013)
The rapid growth of the off-premise catering makes it essential that caterer obtain customer satisfaction for long term survival. Customer satisfaction can be seen when they create favorable future post-purchase action such as repeat the experienced service and they disseminate the positive information to others. From the above notion, this study attempted to identify how quality and monetary price is perceived in relation to satisfaction and post-purchase action in off-premise catering. A questionnaires were distributed to 250 customers from 10 selected off-premise catering in Shah Alam. A series of analyses using descriptive and inferential were used to analyze the data. The results indicate both antecedents have a positive effects on the customer satisfaction and post-purchase action. Results of this analysis will contribute to the services marketing theory by providing additional insights into quality and price, satisfaction, post-purchase action. It will also helps caterers to develop and implement market-oriented service strategies for increasing their profit. Thus, caterers should consider the quality and price dimensions that elicit customer satisfaction and post-purchase action.